Economic Reforms of the Soviet State in the Years of Reconstruction - Eshmamatov Alizod (Procedia of Social Sciences and Humanities, 2022)
In the mid-1980s, the Soviet state implemented a program of reforms that went down in history as "reconstruction." The history of this program is connected with the personality of Mikhail Gorbachev, who was elected Secretary-General of the Central Committee of the CPSU in March 1985. The election of Mikhail Gorbachev, a young member of the highest political leadership at the time, was a sign that the party apparatus was trying to change the declining totalitarian regime a bit. The beginning of radical reforms in public administration, and broad socio-political and economic changes was connected with the decisions of the April plenum of the Central Committee of the CPSU. The leadership sought to develop the state through reforms, taking into account the current crisis in all spheres of the USSR.